A Sodium Polysulfide Battery with Liquid/Solid Electrolyte: Improving Sulfur Utilization Using P2S5 as Additive and Tetramethylurea as Catholyte Solvent. Issue 3 (9th January 2020) - Medenbach, Lukas; Hartmann, Pascal; Janek, Juergen; Stettner, Timo; Balducci, Andrea; Dirksen, Cornelius; Schulz, Matthias; Stelter, Michael; Adelhelm, Philipp
Abstract : Herein, the proof of concept of a sodium polysulfide battery consisting of two electrode chambers being separated by a solid electrolyte is described. The concept is suited for dissolved polysulfide cathodes and has the advantage that both half reactions can be optimized separately. The formation of solid sulfide discharge products is identified as the major limiting factor for cell cycling. This issue can be alleviated by adding solid P2 S5 . Further improvement can be achieved by replacing diglyme (2G) as the cathode compartment solvent with tetramethylurea (TMU). Using TMU, the cell cycles with Coulombic efficiencies >99% and capacities of 800 mAh g −1 are maintained for at least 30 cycles. Viscosity, density, conductivity, and the electrochemical stability window values of the 2G‐ and TMU‐based electrolytes are compared. The latter shows higher viscosity (2.806 vs 1.603 mPa s), higher density (1.016 vs 0.996 g cc −1 ), and higher conductivity (4.27 vs 1.45 mS cm −1 ). The oxidative stability limit of the TMU electrolyte is 3.2 V versus Na + /Na, which is sufficient for polysulfide redox reactions. Vis spectroscopy is used to follow the electrode reaction. In case of TMU, the reaction is based on the redox activity of S3 − radicals (blue coloration of the catholyte solution). Abstract : A Na/polysulfide cell concept with two electrolyte chambers separated by Na‐β″‐aluminate is discussed. The concept allows tailoring of the electrolyte formulation for both half reactions. For the positive electrode, sulfide precipitation is effectively mitigated using P2 S5 as an additive, and cycle life is improved using tetramethylurea (TMU) as a solvent. This proof‐of‐concept study could be interesting for developing stationary energy stores.